PROMIS Correlates With Legacy Outcome Measures in Patients With Neck Pain and Improves Upon NDI When Assessing Disability in Cervical Deformity. Issue 14 (15th July 2019) - Johnson, Bradley; Stekas, Nicholas; Ayres, Ethan; Moses, Michael J.; Jevotovsky, David; Fischer, Charla; Buckland, Aaron J.; Errico, Thomas; Protopsaltis, Themistocles
Abstract : Study Design: Retrospective cohort study. Objective: To evaluate the ability of patient reported outcome measurement information system (PROMIS) assessments to capture disability related to cervical sagittal alignment and secondarily to compare these findings to legacy outcome measures. Summary of Background Data: PROMIS is a validated patient-reported outcome metric that is increasing in popularity due to its speed of administration relative to legacy metrics. The ability of PROMIS to capture disability from sagittal alignment and baseline health status in patients with neck pain has not been investigated. Methods: Patients presenting with a chief complaint of neck pain from December 2016 to July 2017 were included. Demographics and comorbidities were retrospectively collected. All patients prospectively completed the neck disability index (NDI), EQ-5D, visual analog scale (VAS) neck, VAS arm, PROMIS physical function, PROMIS pain intensity, and PROMIS pain interference metrics. Cervical sagittal alignment parameters were measured on standing X-rays. The correlations between outcome measures, health status indexes, psychiatric diagnoses, and sagittal alignment were analyzed. Results: Two hundred twenty-six patients were included. The sample was 58.4% female with a mean age of 55.1 years. In patients with neck pain, PROMIS physical function correlated strongly with the NDI (r = −0.763, P  < 0.01), EQ-5D (r = 0.616, P  < 0.01), VAS neck pain (−0.466, P  < 0.01), and VAS arm pain (r = −0.388, P  < 0.01). One hundred seventy-seven patients (69.96%) were included in the radiographic analysis. 20.3% of the radiographic cohort had cervical deformity and in this group, less cervical lordosis correlated with PROMIS pain intensity and EQ-5D but not NDI. In patients without cervical deformity, no outcome metric was found to correlate significantly with cervical alignment parameters. Conclusion: PROMIS domains correlated strongly with legacy outcome metrics. For the whole cohort, sagittal alignment was not correlated with outcomes. In patients with sagittal cervical deformity, worsening alignment correlated with PROMIS pain intensity and EQ-5D but not NDI. Level of Evidence: 3 Abstract : The ability of PROMIS to capture disability from cervical sagittal malalignment is unknown. Correlations between PROMIS domains and legacy outcome metrics with cervical sagittal alignment parameters were analyzed. PROMIS domains correlated strongly with legacy outcomes and PROMIS Pain Intensity correlated with worsening sagittal alignment in patients with cervical sagittal deformity.